Knightian uncertainty and credit cycles - Eddie Gerba; Dawid Żochowski (European Central Bank (ECB), 2017)
The Great Recession has been characterised by the two stylized facts: the buildup of leverage in the household sector in the period preceding the recession and a protracted economic recovery that followed. We attempt to explain these two facts as an information friction, whereby agents are uncertain about a new state of the economy following a financial innovation. To this end, we extend Boz and Mendoza (2014) by explicitly modelling the credit markets and by modifying the learning to an adaptive set-up. In our model the build-up of leverage and the collateral price cycles takes longer than in a stylized DSGE model with financial frictions. The boom-bust cycles occur as rare events, with two systemic crises per century. Financial stability is achieved with an LTV-cap regulation which smooths the leverage cycles through quantity (higher equity participation requirement) and price (lower collateral value) effects, as well as by providing an anchor in the learning process of agents.
Keywords: G14; G17; G21; G32; E44; E58; 330; uncertainty; financial engineering; deregulation; leverage forecasting; macroprudential policy